Dendritic cells tolerized with adenosine A2AR agonist attenuate acute kidney injury - Li, Li; Huang, Liping; Ye, Hong; Song, Steven P.; Bajwa, Amandeep; Lee, Sang Ju; Moser, Emily K.; Jaworska, Katarzyna; Kinsey, Gilbert R.; Day, Yuan J.; Linden, Joel; Lobo, Peter I.; et al. (The Journal of Clinical Investigation, 2012)
DC-mediated NKT cell activation is critical in initiating the immune response following kidney ischemia/reperfusion injury (IRI), which mimics human acute kidney injury (AKI). Adenosine is an important antiinflammatory molecule in tissue inflammation, and adenosine 2A receptor (A2AR) agonists protect kidneys from IRI through their actions on leukocytes. In this study, we showed that mice with A2AR-deficient DCs are more susceptible to kidney IRI and are not protected from injury by A2AR agonists. In addition, administration of DCs treated ex vivo with an A2AR agonist protected the kidneys of WT mice from IRI by suppressing NKT production of IFN-γ and by regulating DC costimulatory molecules that are important for NKT cell activation. A2AR agonists had no effect on DC antigen presentation or on Tregs. We conclude that ex vivo A2AR–induced tolerized DCs suppress NKT cell activation in vivo and provide a unique and potent cell-based strategy to attenuate organ IRI.